Psychology and Law: Research for practice (De Gruyter, 2020)
Scope The Conference Proceedings of the Annual Conference of the European Association of Psychology and Law, 2019, will consist of empirical researches, meta-analytic reviews and systematic reviews of topics dealing with Psychology and Law (e.g., legal decision making, eyewitness). Neither the Editors nor the Publisher will accept responsibility for the views or statements expressed by the authors. The proceeding book is aimed at researchers, academics and professionals in Psychology, Law, Social Work, Forensic Sciences, Educators and, in general, people related with Social Sciences and the Law. The field of psychology is closely linked to legal processes, from forensic evaluation to treatment of offenders, through treatment with victims or risk assessment. Thus, different professionals from different fields must work together and concertedly, not only to be able to know why, and how, criminal conduct occurs, but also to be able to reduce its consequences and possible recidivism. For this reason, the aim of this international conference is to bring together specialists from the fields of Psychology, Law, Social Work, Forensic Science, Educators, and in general, people related to the Social Sciences and the Law. In turn, it is aimed at professionals, researchers and academics.